Kontribusi Lembar Kerja Peserta Didik Berbantukan Model Scaffolding Problem Solving Pada Materi Teori Kinetik Gas dan Pemanasan Global Terhadap Kompetensi Fisika Di Kelas XI SMAN 1 Lubuk Alung - Joviana Marshel; Ahmad Fauzi; Yulkifli Yulkifli (Universitas Negeri Padang, 2016)
Problem-solving competence of students in the competence of knowledge attitudes and skills in learning physics is not optimal. This is because the learners beloum understand and less interested in learning. besides learning the physics itself is too monotonous and lacking in appeal. thus, this research using model Scaffolding problem solving. Problem-solving skills can be improved through the use of learning problem solving. One of them Scaffolding Problem Solving. This type of quasi sampel research with the study design one shot case study. the entire study population of learners class XI SMAN 1 lubuk alung. sample taken by cluster sampling; so the result XI mia 2 was selected as the study sample class that has 33 students. This is a research instrument in the form of an essay writing test for competency knowledge. observation sheets, self-assessment and peer assessment to the competence of the scoring rubric for the attitude and competence skils. Data analysis using the test at level 3 competition. hasil 0.05 significantly all the research shows that using scaffolding model of problem solving there is a significant contribution to the competency learners